Moving Toward Regulation Using Synergetic Play Therapy - Simmons, Johanna (Canadian Journal of Counselling and Psychotherapy, 2020)
Children generally do not possess the complex, expressive language skills needed to communicate the struggles they are experiencing. In response to this, a variety of play therapy models have emerged. This article concentrates on the application of a research-informed model of play therapy delivery called synergetic play therapy (SPT), which combines interpersonal neurobiology, attachment theory, nervous system regulatory principles, mindfulness, physics, and the self of the therapist. By combining this model with child-centred play therapy (CCPT), the author draws on two case study examples to demonstrate the efficacy of the SPT model when it is coupled with CCPT. The findings and case studies suggest that this approach reduces the severity of identified behavioural concerns. Future investigations in this area are recommended given the gap in the literature regarding combining SPT and CCPT.